Uji Aktivitas Antioksidan Ekstrak Etanol Buah Andaliman (Zanthixylum acanthopodium DC.) Dengan Metode DPPH - Mahral Effendi S (Program Studi S1 Farmasi, STIKES Senior, Medan, 2020)
Andaliman fruit (Zanthixylum acanthopodium DC) is known to have benefits for treating intestinal tracts, treating nausea, asthma, anti-cancer, antioxidants, high blood pressure, and canker sores. The purpose of this study was to determine whether andaliman fruit has antioxidant activity with the DPPH method. The method used in this research is an experimental method, with the stages of collecting plant material, identifying samples, making simplicia, making reagents, characteristics of simplicia, screening phytochemicals, making extracts from andaliman fruit, preparing tools, testing the antioxidant activity of andaliman fruit extracts with the DPPH method. The antioxidant activity test used the DPPH method and then made a control solution and a Vitamin C solution. In this study, the DPPH solution produced a maximum wavelength of 517 nm. The results obtained showed that andaliman fruit extract had very weak antioxidant activity seen from the IC50 value, which was at a concentration of 239.061 ppm. The results of the phytochemical screening of Andaliman fruit contain secondary metabolites, namely alkaloids, flavonoids, saponins, steroids, glycosides.